Investigation of Prosthetic Feet Friction for Enhanced Stability in Persons With Disabilities: ANFIS Analysis of Rubber-Floor Interaction - Thamer Albahkali; Hany S. Abdo; Ahmed Fouly (IEEE Access, 2024)
Prosthetic feet are essential aids for individuals with disabilities, enabling them to stand and walk. However, current prosthetic foot designs often fall short in terms of material properties, potentially compromising safety on various surfaces. This study examines the impact of different rubber types, specifically their hardness, on the friction between prosthetic feet and flooring materials. We evaluated the static friction coefficients of five rubber types on four different floor surfaces under varying normal loads, utilizing an Adaptive Neuro-Fuzzy Inference System (ANFIS) model. Results demonstrate that rubber hardness and normal load significantly influence the friction coefficient. A decrease in rubber hardness increases the friction coefficient, thereby reducing slippage. Notably, a reduction in rubber hardness enhanced the friction coefficient by up to 62%, while an increase in normal load improved it by 35%. Additionally, dynamic friction coefficients were assessed through robotic locomotion experiments on different flooring surfaces using the various rubber materials. These findings provide valuable insights for enhancing the safety and performance of prosthetic feet.